Human health and economic impact of neurocysticercosis in Uganda - Dupont, Fabian; Trevisan, Chiara; Joyce Moriku Kaducu; Emilio Ovuga; Veronika, Schmidt; Andrea S. Winkler; Brecht Devleesschauwer (Wiley Subscription Services, Inc, 2021)
Objective Neurocysticercosis (NCC), caused by the pork tapeworm Taenia solium, is a major cause of acquired epilepsy in endemic regions. The Republic of Uganda, one of the great‐lakes nations in East Africa, has undergone major strives of political instability in the past century, impeding control of T. solium and other foodborne diseases. Building on data on the epidemiology of NCC, we aimed to assess the health and economic impact of NCC‐associated epilepsy and headache in Uganda. Methods We used DisMod II to generate an internally consistent, complete and age‐stratified set of epidemiological parameters for NCC epilepsy, and subsequently modelled the NCC headache incidence from the NCC epilepsy incidence. The health impact of both conditions was quantified in terms of Disability‐Adjusted Life Years (DALYs), while the economic impact was quantified as the cost of illness associated with direct healthcare costs, patient costs and productivity losses. For both assessments, we adopted an incidence perspective and used 2010 as reference year. Uncertainty was propagated using 100,000 Monte Carlo simulations. Results In 2010, NCC was estimated to cause more than 9000 (CI: 7685–11,071) new cases of epilepsy and nearly 1500 new cases of headache, eventually leading to nearly 3000 deaths. Overall, it was estimated that NCC led to more than 170,000 DALYs (5.2 per 1000 person years; 16 per incident case) and an economic loss of more than USD 75 million (8000 per incident case). Non‐fatal health outcomes were the largest contributors to the overall health impact, while productivity losses dominated the NCC cost of illness. Conclusions NCC imposes a substantial burden on public health and the economy in Uganda with poor attention given to this public health problem. Increased awareness among governments, international agencies, and general public, as well as targeted intervention studies using a One Health approach are needed to reduce the significant burden of NCC in Uganda.
Keywords: disability adjusted life years, epilepsy, neurocysticercosis, socioeconomic impact, Uganda